Calculation and valuation of carbon storage in the high Andean wetland of Chalhuanca, Arequipa (Peru) - Pauca Tanco, Gregory Anthony (2021)
High Andean wetlands are important ecosystems due to their ecosystem services. Carbon storage is a result of the low decomposition rate due to flooded soils and low temperatures. The carbon content stored in the high Andean wetland of Chalhuanca (Arequipa) was estimated and the value of this service was calculated. For this purpose, 30 samples were taken at random, establishing three carbon pools: aboveground biomass (leaves and stems), belowground biomass (roots) and organic soil. The samples were obtained with an auger-type device; each sample was dried at 65°C for at least 24 hours and the carbon content was determined using the Walkey-Black method and calculations and statistical tests were performed. The total carbon stored in relation to the area of the wetland was approximately 795,415.65 tons of CO2. The fraction of carbon per sample is higher in aerial biomass (49%), followed by organic soil (43.1%) and below ground biomass. On the other hand, the amount of carbon stored differs significantly between reservoirs, since organic soil stores the highest amount with 218.3 TC/he (90%), followed by below-ground biomass (roots) with 19.7 TC/he (8%), and above-ground biomass (leaves and stems) with 4.8 TC/he (2%). Finally, the ecosystem service of carbon storage cost 6462.18 U$D/he, for a total of 5703132.34 U$D.